A 10-Year Review of Sunburn Injuries Presenting to the Manchester Adult and Paediatric Specialist Burn Services - Lewis A. Dingle; Poh Tan; Parisha Malik; Samantha McNally (MDPI AG, 2022)
Background: The incidence of sunburn injuries continues to rise despite increased awareness of the risks of sun exposure and availability of sun protection. Whilst not a significant burden on burns care services, patients remain exposed to associated risks for future development of skin malignancies. The aims of this study were to determine the burden and severity of sunburn injury presentations to the Manchester adult and children's burns services. Methods: A 10-year retrospective review was performed of patients with sunburn injuries, presenting to the Manchester burn services between 2010 and 2019 (inclusive). Data were collected from the International Burn Injury Database (iBID), electronic patient record (EPR) and local data collection systems. The data extracted included patient demographics, sunburn characteristics and management of the burn injury including need for admission and any documented surgical interventions. Temporal correlation was determined by linear regression analysis. Results: In total, 131 paediatric and 228 adult patients with sunburn injuries were managed by the Manchester burns services over the 10-year period. Mean % total body surface area burned was low (2.00% and 2.12% in adult and paediatric patients, respectively), with the majority of injuries either superficial or superficial partial thickness. Thirty percent (30.2%) of adult and 40.5% of paediatric patients were admitted with a mean length of stay of 3.51 and 1.11 days, respectively. The presentation of sunburn injuries progressively increased over the study period with a peak in 2017 (n = 58). Similar trends in patient demographics, burn size and depth and temporal trends were observed in national data from the same period for both adult and paediatric patients. Conclusion: This 10-year retrospective cohort study demonstrates an increasing trend of sunburn injury presentations to the Manchester specialist burns services; a pattern replicated in national data from England and Wales. The majority of sunburn injuries do not present to specialist burn services; therefore, these reported injuries reflect only a fraction of the true burden of sunburn nationwide. Despite increased awareness, an obvious need for enhanced public awareness campaigns regarding sun protection is therefore needed to address this trend. The educational and preventative role of burns care services is a key component in tackling both consequences of burn injuries themselves and associated risks such as future skin cancer development.